Enhancement of Crashworthiness Parameters Using a Bitubular Tube with Various Tube Lengths - Abdulqadir, Samer Fakhri; Ahmed, Zinah Jumaah; Khalaf, Wekar M.; Alrawi, Dhafer Fakir; Dawood, Haitham Kamil (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
The study aims to investigate the effect of numerical analysis on a bitubular circular tube subjected to dynamic loading. To compare its performance, a circular monotube specimen with a perimeter of 300 mm, a thickness of 2 mm, and a length of 350 mm was used as a reference. The bitubular circular tubes consist of two tubes, an inner and an outer. The outer tube's perimeter was initially set at 350mm with a wall thickness of 1 mm, while the inner tube had a perimeter of 250 mm and a thickness of 1 mm. The outer perimeter was gradually decreased by 10 mm, while the inner tube's perimeter was simultaneously increased by 10 mm for each configuration. This process was repeated until reaching perimeter lengths of 305 mm and 295 mm for the outer and inner tubes, respectively. The outer tube's length remained fixed at 350 mm, the same as the reference tube's length. The inner tube's length was initially kept identical to the outer tube while changing the tube's perimeter, aiming to maintain the same mass insofar as was possible compared to the reference tube. The inner tube of each configuration was then shortened by 10 mm until reaching a length of 300 mm. Six specimens were selected as the best performers based on the lowest load and highest crush force efficiency (CFE) criteria using the complex proportional assessment (COPRAS) technique. The results revealed that the best design was the bitubular configuration with an outer tube perimeter of 340 mm, an inner tube perimeter of 260 mm, and an inner tube length of 320 mm. This configuration achieved a 44% reduction in peak force, a 19% increase in crash force efficiency (CFE), and a 3.7% decrease in mass compared to the reference monotube. These findings indicate that the chosen bitubular configuration achieves a desirable balance of reduced peak force and improved crash force efficiency, making it a promising design for energy absorption and occupant protection during collisions.